Non-party actors' political communication styles (study case: Anis Baswedan's leadership) - Asgaf, Asrianto; Anom , Erman (The International Journal of Politics and Sociology Research, 2023)
This research aims to determine the political communication style used by Anis Baswedan in political audiences and in political leadership or in gaining momentum for leadership and authority to manage the government. And the object of this research is a study of the political communication style used by Anis Baswedan as a political leader, candidate and government in an effort to influence public opinion, as well as win elections, or achieve their political goals. Political communication style is related to how a leader projects himself as a figure who has credibility, integrity and strong leadership in the eyes of the public. In this research, a concept is projected that is used to explain the political communication style of non-party actors in the case study of Anis Baswedan's leadership. There are various theories that try to explain various aspects of political communication styles. The method in this research used a qualitative descriptive method. The data collection techniques are observation, interviews and documentation as well as other literature reviews. The data is obtained and analyzed carefully. The results of this research are the figure of political actor Anis Baswedan in carrying out his political communication style as well as possible and ideally as a public figure in order to gain sympathy from the public or society in every stakeholder.